Investigation of Influencing Process Parameters to Energy and Exergy Efficiencies of a Coal Fired Thermal Power Plant using Cycle Tempo - Patel, SSL; Agrawal, GK (International Journal of Computer Sciences and Engineering, 2025)
This work is carried out to study the effect of various process parameters upon plant efficiencies in order to prioritise them for posssible improvement in utilisation of input energy. In the process a flow sheet computer program “Cycle Tempo 5” has been used for modeling and simulation of a 250MW coal fired thermal power plant. Effects of individual parameters upon plant energy and exergy efficiency are investigated and the energy and exergy balance diagram is also drawn. The condenser pressure is found to be the most influencing factor which on changing from 0.1bar to 0.12bar both the energy and exergy efficiency reduces by 0.4%. Main steam pressure, reheat steam temperature and pressure are also affecting the performance considerably while main steam temperature is found to be the least affecting parameter among the studied one. Energy balance diagram clearly shows that the major portion of energy loss takes place at condenser while boiler is the component causing major exergy loss as seen from the exergy balance diagram